2010
DOI: 10.1002/mus.21707
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number index (MUNIX): A novel neurophysiological technique to follow disease progression in amyotrophic lateral sclerosis

Abstract: Motor unit number estimation techniques in amyotrophic lateral sclerosis (ALS) patients are technically challenging and time-consuming. The Motor Unit Number Index (MUNIX) is a novel technique based on surface-EMG recordings and requires only 3-5 minutes per muscle. The objective was to explore the feasibility of longitudinal MUNIX measurements in ALS patients. In seven patients enrolled in a clinical trial, eight muscles were studied every 2 months for up to 15 months in addition to the revised ALS-functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 24 publications
(30 reference statements)
10
95
1
3
Order By: Relevance
“…Our findings, based on two time points for each patient, showed decline in CMAP and MUNIX, but not a significant decline in IS-MUNE. MUNIX, expressed as percent change from baseline, declined in average by 7.48% (SEM 2.25) per month, in accordance with previously reported range of 2.75-10% per month (Ahn et al, 2010;Nandedkar et al, 2010;Neuwirth et al, 2010). The absence of significant reduction in IS-MUNE may be due to its large variance between subjects and low reproducibility (high MPD) which increases the likelihood that the subjects ranking order would change by the second measurement.…”
Section: Potential Of Mune As Biomarker Of Disease Progressionsupporting
confidence: 85%
“…Our findings, based on two time points for each patient, showed decline in CMAP and MUNIX, but not a significant decline in IS-MUNE. MUNIX, expressed as percent change from baseline, declined in average by 7.48% (SEM 2.25) per month, in accordance with previously reported range of 2.75-10% per month (Ahn et al, 2010;Nandedkar et al, 2010;Neuwirth et al, 2010). The absence of significant reduction in IS-MUNE may be due to its large variance between subjects and low reproducibility (high MPD) which increases the likelihood that the subjects ranking order would change by the second measurement.…”
Section: Potential Of Mune As Biomarker Of Disease Progressionsupporting
confidence: 85%
“…Prospective studies showed a progressive decrease in MUNIX values in small groups of ALS patients, indicating a decrease in the motor unit population Neuwirth et al, 2010). Furtula et al demonstrated that the progressive reduction in MUNIX was comparable to the reduction of incremental stimulation MUNE (IS-MUNE) in a prospective study assessing the ADM muscle in 13 patients with ALS [Furtula et al, 2013].…”
Section: Motor Unit Number Index (Munix) Analysis Is a Technique Devmentioning
confidence: 97%
“…However, there are considerable CMAP data as a CMAP is needed in order to calculate the MUNE. And, in fact, the median and ulnar CMAPs actually show substantial decline over time in most patients with ALS, as demonstrated by 2 recent MUNEfocused studies [46,47]. The biggest challenge to the CMAP is its reliability, which is sensitively dependent on electrode positioning, limb and hand positioning, and temperature.…”
Section: Compound Motor Action Potential and The Neurophysiological Imentioning
confidence: 99%